Analisis Praktik Persaingan Usaha Tidak Sehat di Platform Digital E-Commerce di Indonesia: Tinjauan Hukum Persaingan Usaha - Ratna Dewi; Afriyanto Setiawan; Leo Sekar Indra; Gabrielle Evania Cahyadi; Unik Bunga Diva; Boyke Christ Purba (PT PUSTAKA CENDEKIA GROUP, 2025)
The development of digital e-commerce platforms in Indonesia has fundamentally transformed the business landscape. However, this rapid growth has also given rise to various unfair business competition practices that potentially harm consumers and other business actors. This study aims to analyze various forms of unfair business competition practices in Indonesian e-commerce platforms and evaluate the effectiveness of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition in regulating digital platforms. The research method used is normative juridical with statutory and case approaches. The research findings indicate that unfair competition practices in Indonesian e-commerce platforms include predatory pricing, price discrimination, exclusive agreements, and abuse of dominant position. This study recommends the need for more specific regulatory revisions governing the digital economy and strengthening the role of KPPU in supervising e-commerce platforms.